Suicide prevention training for allied health professionals within healthcare environments: A scoping review - Jade Rentzoulis; Amanda Gilmore; Rowena Saheb; Arianne C. Reis (PLoS ONE, 2025)
Despite the knowledge that many individuals who die by suicide have contact with a health professional a short time prior to their death, the delivery and quality of clinical care is reportedly variable. Those affected by suicide have reported poor management of suicidal behavior, noting that many health professionals lack an understanding of, and carry negative attitudes toward suicidality. Though quality crisis care and follow-up treatment have shown to reduce the frequency of repeated suicide attempts, organizational barriers and lack of appropriate training mean these are not always provided. This review aimed to synthesize the evidence on suicide prevention training delivered to allied health professionals within healthcare environments. A scoping review of empirical research on the topic was undertaken using the JBI methodological framework, followed by a content synthesis of the evidence to explore the key characteristics of training and their outcomes. The databases included in the search were MEDLINE, CINAHL, PSYCHinfo, Scopus, and Embase. Final search and extraction from all databases were conducted on the same day in April 2021 and repeated in July 2023. The extracted data was collated and presented in tabular form to facilitate analysis. The review identified 33 relevant articles. The evidence base was largely heterogenous, involving a wide range of training types and underpinning frameworks. The measurement tools used to assess effectiveness of training were mostly not validated, with predominant use of short-term pre-post measures frequently based on perceptions of change rather than objective measures of behavior change. Significantly, evidence presented was generally weak and inconsistent between studies. This review highlighted significant gaps in current knowledge within the field of suicide prevention training delivered to allied health professionals. Investing in efficacious training and professional development opportunities is key to building the capacity to reduce suicide mortality in our community.